Systematic research of the remains of a 2nd-century Roman shipwreck off the island of Ilovik (In situ, 2024)
In 1962, well-preserved cargo of a sunken Roman ship was discovered at the northern entrance to the channel, off the island of Sv. Petar. Until 1970, the surface of the site was thoroughly looted, but many interesting finds were still found during the rescue excavations conducted from 1978 to 1980 under the leadership of Marijan Orlić. The first systematic research campaign was conducted in 2022, in cooperation between the University of Zadar and the University of Rhode Island. The research resulted in new information about the ship and its cargo. Fourteen complete or almost complete amphorae were discovered in the western part of the site. The wooden remains are rather poorly preserved due to the rocky base and small amount of sediment.
Keywords: Ilovik; shipwreck; Antiquity; amphoras